Newspaper cuttings relating to preparations for Easter Week 1916, memoranda by Eoin Mac Neill, and 1966 Thomas Davis lectures by Florence O'Donoghue and F. X. Martin - O'Donoghue, Florence, 1895-1967; Ó Lúing, Seán, 1917-2000; Gwynn, Denis, 1893-1973 (1961)
Includes series of articles by Piaras Béaslaí and Desmond Ryan.
Keywords: Mac Neill, Eoin, -- 1867-1945; Pearse, Padraic, -- 1879-1916.; Hobson, Bulmer; Casement, Roger, -- 1864-1916; Ireland -- History -- Easter Rising, 1916